2007
DOI: 10.1007/bf02912895
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant vitamins in urolithasis

Abstract: The present, study was conducted to determine the level of malondialdehyde (MDA) as an index of free radial induced lipid peroxidation and antioxidant vitamins -vitamins A, vitamin C and vitamin E in Address for Correspondence :Dr. W. Gyaneshwar Singh Professor and Head, Department of Biochemistry Regional Institute of Medical Sciences, Imphal, Manipur. Pin-795004 • E-mail : wg_singh@yahoo.co.in initiation of calcium oxalate formation are still not known. However the oxidant (free radical production) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…Hyperoxaluric treatment caused extensive CaOx crystal deposition in kidneys of untreated rats accompanied by oxidative damage as reflected from increased levels of markers of oxidative injury such as MDA and protein carbonyl content and decreased activities of antioxidant enzymes along with GSH level. MDA is a major end product of lipid peroxidation in membrane fatty acids representing oxidative tissue damage caused by ROS resulting in structural alteration of membrane with release of cell and organelle contents, loss of essential fatty acids with formation of cytosolic aldehyde and peroxide products (Kato et al, 2007). In the present investigation, the level of MDA was found to be significantly elevated with oxalate exposure in hyperoxaluric rats.…”
Section: Discussionsupporting
confidence: 47%
“…Hyperoxaluric treatment caused extensive CaOx crystal deposition in kidneys of untreated rats accompanied by oxidative damage as reflected from increased levels of markers of oxidative injury such as MDA and protein carbonyl content and decreased activities of antioxidant enzymes along with GSH level. MDA is a major end product of lipid peroxidation in membrane fatty acids representing oxidative tissue damage caused by ROS resulting in structural alteration of membrane with release of cell and organelle contents, loss of essential fatty acids with formation of cytosolic aldehyde and peroxide products (Kato et al, 2007). In the present investigation, the level of MDA was found to be significantly elevated with oxalate exposure in hyperoxaluric rats.…”
Section: Discussionsupporting
confidence: 47%
“…SOD, GSH, CAT, and MDA are the marks for oxidative stress because they are involved in the antioxidant defense system leading to potential damage due to oxidative stress [30][31][32]. In this experiment, supplementation with 90 mg/kg Zn-Gly increased the activity of Cu/Zn-SOD and GSH-P X and lowered the level of MDA in livers of 21-day broilers.…”
Section: Discussionmentioning
confidence: 86%
“…Lipid peroxidation represents oxidative tissue damage caused by hydrogen peroxide, superoxide anions and hydroxyl radicals, resulting in structural alteration of the membrane, release of cell and organelle content and loss of essential fatty acids with formation of cytosolic aldehyde and peroxide products (24). MDA is a secondary product generated during the oxidation of polyunsaturated fatty acids, which has been frequently measured as an indicator of lipid peroxidation and oxidative stress in vivo (25).…”
Section: Resultsmentioning
confidence: 99%
“…MDA is a secondary product generated during the oxidation of polyunsaturated fatty acids, which has been frequently measured as an indicator of lipid peroxidation and oxidative stress in vivo (25). Numerous studies have observed that strenuous physical exercise induces increases in the MDA concentration in tissues (24,26,27). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%